2013
DOI: 10.1136/jfprhc-2011-100284
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of unprotected sexual intercourse among women who inject drugs or who have sexual partners who inject drugs in St Petersburg, Russia

Abstract: Objectives To assess risk for unintended pregnancy, this study describes the correlates of unprotected sexual intercourse (UPSI) among women who inject illicit drugs or who have sexual partners who inject drugs in St Petersburg, Russia. Methods Data from a cross-sectional survey and biological test results collected between 2005 and 2008 from 202 Russian women (143 drug injectors and 59 non-drug injectors) were analysed. Multivariate regression was used to investigate the correlates of UPSI occurring at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Thirty percent of currently pregnant WIDUs found out about their pregnancies after 12 weeks of gestation, eliminating the opportunity to cease drug use during the first trimester or legally terminate the pregnancy. Other studies conducted in Saint Petersburg have demonstrated that WIDUs need comprehensive intervention programs aimed at primary, secondary, and tertiary prevention of HIV infection; 30 , 31 prevention of unplanned and unwanted pregnancies; 11 , 12 and assistance in changing risk behaviors in pregnant WIDUs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty percent of currently pregnant WIDUs found out about their pregnancies after 12 weeks of gestation, eliminating the opportunity to cease drug use during the first trimester or legally terminate the pregnancy. Other studies conducted in Saint Petersburg have demonstrated that WIDUs need comprehensive intervention programs aimed at primary, secondary, and tertiary prevention of HIV infection; 30 , 31 prevention of unplanned and unwanted pregnancies; 11 , 12 and assistance in changing risk behaviors in pregnant WIDUs.…”
Section: Discussionmentioning
confidence: 99%
“…Age and education were found to be important confounders in other studies. 12 Little is known about parental status as a potential confounder of the association between pregnancy and active injection drug use and/or sex work, but some evidence indicates it might be a confounder. 23 , 24 All potential covariates were associated both with exposure and the outcomes in bivariate analyses and met the criteria for being potential confounders according to constructed directed acyclic graphs (DAGs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[134][135][136] Low contraceptive use and high unmet need for family planning has been documented in several studies. 63,[137][138][139] Further investigation is needed, particularly into how sexual and reproductive health services and parenting skills-building can be integrated into substance use treatment programmes and other health interventions serving people who use drugs. [140][141][142] High rates of abortion have been reported among women who use drugs, some of whom are also sex workers, however, reduction in abortion-related risks and integration of family planning and post-abortion care in this population has not adequately been documented.…”
Section: Women Who Use Drugsmentioning
confidence: 99%
“…Heavy sporadic drinking in women who injected drugs or who had sexual partners who injected drugs increased the risk of unprotected sexual intercourse. 37 Recently, Dr. Abdala completed a study focused on evaluating the efficacy of an alcohol and HIV risk behavior reduction intervention among patients at sexually transmitted disease (STD) clinics in St. Petersburg.…”
Section: An Overview Of Presentationsmentioning
confidence: 99%